The Pengaruh Konsep Diri dan Kemandirian Belajar Terhadap Motivasi Belajar Peserta Didik - Rediah, Hasiati Lampitama; Gumilar, Rendra; Hermawan, Yoni (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to analyze the influence of self-concept, independent learning, and family environment on the learning motivation of high school students. This study uses a quantitative method with a survey approach. The research sample consisted of 207 tenth grade students from SMA Negeri 5 Tasikmalaya who were selected using the proportionate random sampling technique. Data were collected through questionnaires and analyzed using SPSS 26. The regression test results show that self-concept and independent learning have a positive and significant effect on learning motivation, with significance values of 0.004 and 0.000, respectively. The family environment also has a significant effect with a sig value of 0.000. The F test shows that the three independent variables simultaneously have a significant effect on learning motivation (sig = 0.000). The coefficient of determination (R²) of 0.599 indicates that 59.9% of the variation in learning motivation can be explained by the three variables. These findings confirm that internal and external factors play an important role in increasing students' learning motivation. Therefore, educators and parents need to provide optimal support to create a conducive learning environment.